Learning about adaptation possibilities by talking to Kenyan female and male farmers separately - Kristjanson, Patricia; Bernier, Quinn; Bryan, Elizabeth; Ringler, Claudia; Meinzen-Dick, Ruth S.; Mango, Joash; Kovarik, Chiara; Haglund, Eric; Quiros, Carlos; Herrero, Mario; Rufino, Mariana; Silvestri, Silvia; et al. (International Food Policy Research Institute, 2015)
In Kenya and elsewhere, male and female farmers have different roles and responsibilities on the farm. What this means in terms of how they will adapt their farming practices in the face of a changing climate, and what governments, development agencies, NGOs, and researchers can do to facilitate this, is not so well known. We set out to explore gender differences in how men and women perceive climate change and its impacts, and the ways they are responding to these changes by interviewing a woman and man in 400 Kenyan rural farming households. We asked the same set of questions of the men and women, and found interesting similarities and differences in their answers.